THE METHOD TO OBTAIN COMPLEX MINERAL-ORGANIC BIOFERTILIZER BASED ON BIRD DROPPINGS - Esenbaeva, A.E.; Ten, O.A.; Balpanov, D.S. (Eurasian Journal of Applied Biotechnology, 2014)
Organic fertilizers (manure, litter and non-litter bird droppings, sapropel, etc.) help to increase the humus content in the soil and are an essential tool to restore and to improve the soil fertility. Litter bird droppings is a valuable high-performance, full fertilizer. Considering the impact on the crop yields, the substances that make up the bird droppings, can be compared with analogous substances of mineral fertilizers. Microorganisms introduced into the soil in the composition of complex fertilizers and fertilizers based on monocultures, enhance biological activity of the soil; improve the soil from plant pathogens; promote activation of plant-microbe interactions, help to obtain high yields of organic farming; enhance the recovery of microbiocenosis of the soils, upset due to the human impact. As a result of the work performed, the optimal conditions of fermentation of litter bird droppings, the effectiveness of the introduction of micro-organisms at different stages of fermentation of litter bird droppings was assessed. It is shown that the biologically active microorganisms are retained when added to mature compost. The experimental batch based on highly active strains of fungicide microorganisms Bacillus subtilis S-2 and the phosphate-mobilizing bacteria Bacillus megaterium F-1 immobilized on the fermented bird droppings is promising to be used as a mineral complex organic bio-fertilizer.